Quantum Message Distribution - 罗明星 陈秀波 邓云 杨义先 (Communications in theoretical physics, 2013)
The semiquantum techniques have been explored recently to bridge the classical communications and the quantum communications. In this paper, we present one scheme to distribute the messages from one quantum participate to one weak quantum participate who can only measure the quantum states. It is proved to be robust by combining the classical coding encryption, quantum coding and other quantum techniques.